1996
DOI: 10.1111/j.1440-1843.1996.tb00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Broncho‐mediastinal fistula following perforation of the oesophagus

Abstract: We present a 63-year old female with mediastinitis following an esophageal perforation, possibly favoured by an oesophageal motility-disorder and the use of non-steroidal anti-inflammatory drugs, who developed a broncho-mediastinal fistula in the left main bronchus. She was successfully treated with intravenous antibiotics, a cervical oesophagostomy and secondary isoperistaltic coloplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Neonatal bronchomediastinal fistulas are extremely rare and usually are associated with iatrogenic injury [1][2][3][4]. In this case, we suspect that the injury occurred after intubation and during endotracheal tube suctioning.…”
Section: Discussionmentioning
confidence: 81%
“…Neonatal bronchomediastinal fistulas are extremely rare and usually are associated with iatrogenic injury [1][2][3][4]. In this case, we suspect that the injury occurred after intubation and during endotracheal tube suctioning.…”
Section: Discussionmentioning
confidence: 81%
“…Previous reports have theorised that an oesophageal perforation secondary to barotrauma from vomiting (Boerhaave's syndrome) [3, 18] or even pill dysphagia (and resultant effects of corrosive additives) [2] may explain the presence of mediastinal and retropharyngeal free air. Conditions causing oesophageal dysmotility have been implicated secondarily contributing to increased intraoesophageal pressure [19]. A recent retrospective study identified up to ten percent of patients diagnosed with SPM had a proven oesophageal perforation found on endoscopy, in a contrast study, or discovered during surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…Referral to an otolaryngologist for flexible nasendoscopy (FNE) is recommended to look for pharyngeal perforation or injury, followed by a gastrografin swallow in the first 24 hours to assess for oesophageal injury. While extensive workup is not recommended in all cases [25], the combination of the chemical nature and mechanism of administration of the substances involved in drug-related SPM warrants thorough investigation in even the most stable patients [2, 11, 1719, 23]. The only case in the literature requiring invasive intervention was that of pneumothorax in addition to pneumomediastinum [13], and the only reported case of recurrence of pneumomediastinum was that involving oesophagitis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with extensive pulmonary blebs also have a relative contraindication to TT placement because of the risk of bronchial fistula formation. [47] Elective or semi-elective TT placement should be avoided in patients with clinically significant coagulopathy and consideration should be given to normalization of coagulation parameters prior to commencing with the procedure.…”
Section: Introductionmentioning
confidence: 99%